Workplace spirituality and counterproductive work behaviour (CWB): A Malaysian perspective - Mat, Norazuwa; Md. Naser, Nooraida (2012)
﻿The concept of counter-productive work behaviour (CWB) has been the focus attention from organisation researchers and practitioners. Counterproductive work behaviours are prevalent among employees in many organizations today, but much of it apparently goes unnoticed, unreported, or both. With regard to these CWB issues, is it caused by an individual’s lack of control or spirituality resulting in undesirable acts? Should a person be naturally aware of the ways to control their behaviour? According to the Counselling Theory by Imam Al-Ghazali, apart from an individual’s ability to control his / her emotions, an individual also should properly be able to control his / her heart that is inner spirituality. The heart is a source of the good and bad of human life. Once the heart is damaged, the lust is inclined towards the negative and the soul is not at peace. Thus, the purpose of this study is to investigate the relationship between work spirituality and counterproductive work behavior. Results from regression analyses indicated that two dimensions in workplace spirituality (meaning at work and work unit community) are making unique contribution to the prediction of CWB. Work unit community is the strongest influence to counterproductive work behaviour.